Food Security in Algeria: An Analytical Study - Bouziane, Fatiha; Laallam, Abdelkader; Oussedik, Mohamed Imad; Ouassaf, Saidi; Khababa, Nourredine (Journal of Ecohumanism, 2024)
The present research aims to investigate the state of food security in Algeria and its ability to confront internal and external shocks. A descriptive analytical approach was used to analyze various indicators and figures that reflect the food security state in Algeria. The results of this study show that food security in Algeria is at an acceptable level, but it is fragile and not strong enough to face shocks due to Algeria's heavy dependence on imports to meet its food needs, as well as not giving great importance to the farming segment as a major factor in achieving food security.